2010
DOI: 10.1002/hyp.7668
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale climatic influences on precipitation and discharge for a British river basin

Abstract: Abstract:This article aims to identify the large-scale climate variables that yield significant statistical relationships with precipitation and discharge for a British river basin (Dyfi). Ranked correlation analysis was performed between gridded ERA-40 atmospheric data and Dyfi precipitation and discharge for individual months. Precipitation and discharge demonstrate significant negative correlation with mean sea level pressure (MSLP). Strongest MSLP correlation areas move from north of Britain in winter to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
4
7
0
Order By: Relevance
“…Streamflows in northern European rivers are generally positively correlated with the NAO, whereas streamflows in central and southern rivers show the opposite relationship. A positive and significant relationship (r > 0.6) was found during winter in Scandinavia (Shorthouse and Arnell, 1997), and similar values were found for river basins in Britain (Philips et al, 2003;Lavers et al (2010). A significant negative relationship (r = −0.75) was reported by Rimbu et al (2002) for the Danube River in central Europe, and moderate negative correlations (r ≈ −0.4) have been reported (Pekarova and Pekar, 2004) for various sites in the Hron basin, Slovakia.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Streamflows in northern European rivers are generally positively correlated with the NAO, whereas streamflows in central and southern rivers show the opposite relationship. A positive and significant relationship (r > 0.6) was found during winter in Scandinavia (Shorthouse and Arnell, 1997), and similar values were found for river basins in Britain (Philips et al, 2003;Lavers et al (2010). A significant negative relationship (r = −0.75) was reported by Rimbu et al (2002) for the Danube River in central Europe, and moderate negative correlations (r ≈ −0.4) have been reported (Pekarova and Pekar, 2004) for various sites in the Hron basin, Slovakia.…”
Section: Introductionsupporting
confidence: 55%
“…This explains the close relationship of summer and autumn streamflow to the previous winter NAO, especially in the southern basins with larger impoundment capacities (Tagus, 11 012 hm 3 ; Guadiana, 8635 hm 3 ; and Guadalquivir, 8280 hm 3 ): the majority of those rivers with retention capacity exceeding the mean annual discharge for the study period showed a sustained response to the winter NAO during the rest of the year. The strong correlations between the winter NAO index and streamflows during May, June and July in the Pyrenean sub-basins reflect the importance of snow accumulation and melting processes in the Pyrenean rivers (López-Moreno and García-Ruiz, 2004), and the inertia that these processes induce in the runoff yield.…”
Section: Spatial and Temporal Variabilitymentioning
confidence: 99%
“…It is possible that some of these measures might not have been needed had an effective seasonal hydrological forecast been available, as such forecasts can potentially provide an estimate of river flows and water resources for a lead time of several months ahead. A number of authors have explored the potential for seasonal hydrological forecasting in the UK, with many investigating statistical relationships between large‐scale North Atlantic climate indices (such as the North Atlantic Oscillation) and seasonal rainfall or river flow anomalies (Lavers et al ., ,; Macgregor and Phillips, ; Svensson and Prudhomme, ; Wedgebrow et al ., ; Wilby, ). Lavers () is one of the few to have explored direct use of coupled ocean–atmosphere model output with hydrological models for seasonal hydrological forecasting in the UK, perhaps because of the perceived lack of skill in seasonal weather forecasts in extratropical regions beyond a lead time of 1 month (Lavers et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive and negative NAO phases particularly affect runoff behaviour, dry and wet periods (Lavers et al . ), which particularly affects TOC transport. Our results suggest that NAO has a greater effect on spring and autumn TOC fluxes in the River Oulujoki system and TOC transport from tributaries and areas near the main channel.…”
Section: Discussionmentioning
confidence: 99%